FROM CONCEPT TO MEASUREMENT: A SYSTEMATIC APPROACH TO DEVELOP SCALE FOR ASSESSING BULLYING VICTIMIZATION IN UNIVERSITY STUDENTS (The Research of Medical Science Review, 2025)
Bullying victimization is widespread and considered a significant factor influencing mental health, academic performance, and social interactions among university students. The purpose of this study is to develop an indigenous scale for assessing the expression of bullying victimization among Pakistani university students. Initially, 37 items were elicited using open-ended interviews with 20 randomly selected university students (10 male and 10 female) aged 18 - 25 years. 10 professionals, including clinical psychologists, campus counselors, and research experts with at least five years of experience, validated the scale by evaluating item relevance and cultural appropriateness to ensure content validity. Based on their feedback, the scale was adjusted to a 32-item measure. A pilot study of 20 participants (10 male and 10 female) confirmed the viability of this self-report measure. The scale was further administered to 300 private university students (50% male, 50% female) between 18 and 25 of age (M= 22.41, SD= 2.81) to evaluate its psychometric properties. Exploratory Factor Analysis (EFA) identified three components in the Bullying Victimization Scale (BVS): dominance and control, mocking, and aggression. The Bullying Victimization Scale (BVS) had high internal consistency (α=.93), split-half reliability (r= .86), and good construct validity, revealing a significant positive relationship between bullying victimization and perceived maternal over-protection (r =.12, p <.05). This study sheds light on cultural parenting practices in a collectivistic society by highlighting the connection between bullying victimization among Pakistani university students and parental over-protection. The Bullying Victimization Scale for University Students (BVSU) is a useful tool for recognizing bullying victimization behaviors, which was created specifically for the Pakistani context.